Spatial and temporal patterns, trends and teleconnection of cumulative rainfall deficits across Central America. (10th December 2018) - Muñoz‐Jiménez, Rudy; Giraldo‐Osorio, Juan Diego; Brenes‐Torres, Alonso; Avendaño‐Flores, Isabel; Nauditt, Alexandra; Hidalgo‐León, Hugo G.; Birkel, Christian
Abstract : Central America is a region vulnerable to hydrometeorological threats. Recently, the impacts of droughts caused higher economic losses in comparison to, for example, floods and landslides. This study focuses on the spatio‐temporal behaviour of cumulative rainfall deficits across Central America attempting to provide an historical context to the most recent drought episodes. We developed a long‐term (1950–2014), monthly rainfall data set that merged large‐scale interpolated products with a station observation network to spatially and temporally evaluate the 12‐month Standardized Precipitation Index (SPI12) across the region. We found that El Niño cannot always be associated with drier conditions and that severe droughts are likely to spatially develop from localized phenomena to cover the entire region beyond the Central American drought corridor (CADC). Furthermore, there is not always a clear separation into the Pacific and Caribbean domain in terms of drought behaviour, but generally El Niño episodes can be associated with drier conditions on the Pacific slope and wetter conditions in the Caribbean. We could also show that trends in the SPI series are spatially variable and that more localized significant positive and negative trends exist throughout Central America. For example, central pacific Nicaragua was identified as a hot spot for significant drying conditions related to El Niño. We aim at developing this effort into a near‐real time and publicly available drought monitor in the near future to increase resilience and adaption efforts in the region. Abstract : El Niño episodes mostly produce drier conditions on the Pacific slope and wetter conditions in the Caribbean, but not always. El Niño episodes do not always produce drier conditions as ENSO is not the only teleconnection influencing Central American climate. Until 2014 there is local evidence of statistically significant drying (Pacific and Central Nicaragua, Central Honduras, southern Costa Rica) and wetting (Central Guatemala). Figure shows the December 1998 interpolated SPI12 across Central America, to date recorded as the most severe drought affecting the region.